2019
DOI: 10.1109/access.2019.2946258
|View full text |Cite
|
Sign up to set email alerts
|

AC Surface Flashover and Gas Generation Difference of the Cellulose Insulation Pressboard Immersed in Novel 3-Element Mixed Oil and Mineral Oil

Abstract: Surface flashover fault is one of the most challenge issues in oil-cellulose insulation pressboard system used in power transformer. In this study, a comparative study of the AC surface flashover properties of the novel 3-element mixed oil-cellulose insulation pressboard (3EMO-IP) and mineral oil-cellulose insulation pressboard (MO-IP) was performed under needle-plate and finger-finger electrode, respectively, measurement including dielectric property, surface flashover voltage, damage of cellulose pressboard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Complete orientation of molecules can only be achieved at lower frequencies, and orientation polarization takes longer to reach equilibrium static field values than electronic or atomic polarizations, indicating that it is more difficult to achieve complete orientation. The result is that when frequency increases, ɛ 0 drops as a result of the time delay in polarization orientation [1]. The orientation of the filler and the interfacial polarizations are also affected by the amount of filler present.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Complete orientation of molecules can only be achieved at lower frequencies, and orientation polarization takes longer to reach equilibrium static field values than electronic or atomic polarizations, indicating that it is more difficult to achieve complete orientation. The result is that when frequency increases, ɛ 0 drops as a result of the time delay in polarization orientation [1]. The orientation of the filler and the interfacial polarizations are also affected by the amount of filler present.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible to derive the volume resistivity (q) from the resistance by use the equation. ρ = RA-t (1) where V represents volume resistivity, R represents resistance, A represents the crosssectional area of the sample, and t represents the thickness of the sample…”
Section: Electrical Analysis Of Banana Leaf Rtm Compositementioning
confidence: 99%
See 1 more Smart Citation
“…11 describes the mechanism of creeping flashover voltage occurrence along oil-pressboard interface. Negative charges are formed within the pressboard as it has the higher relative permitivitty than the transformer oil [18]. Then, positive surface charges are attached to the pressboard surface due to the attraction force with the negative charges within the pressboard.…”
Section: Discussionmentioning
confidence: 99%
“…However, few ones deal with their effect on creeping flashover voltage of oil-pressboard insulation. The concept of mixing two types of vegetable oil with the base mineral transformer oil (3-element mixed insulation oil, 3EMO) for enhancing flashover voltage at oil pressboard interface is studied in [18]. It is also reported that using 3EMO impregnated pressboard has a slightly higher relative permittivity and a lower percentage of dissolved gases during flashover.…”
Section: Introductionmentioning
confidence: 99%